Impaired swallowing: a neglected nursing diagnosis? - Mandysova, Petra; Ehler, Edvard; Skvrnakova, Jana (Profese Online, 2011)
The article focuses on the issue of identifying the nursing diagnosis "impaired swallowing". The aim of the article is to highlight the issue of swallowing disorders and to provide information about the importance of screening and about screening options that could facilitate dysphagia identification. At the same time, this type of assessment could become part of a systematic approach to patient care and it could support multidisciplinary collaboration. The mentioned screening methods were identified using three professional databases (EBSCOhost, ProQuest, Journals@Ovid). The analysis of these methods focused on the content of the method, the manner in which the validity of the method was established and thereby on their quality, and also mainly on sensitivity, specificity, and in some cases, on negative predictive value. By using quality screening methods for dysphagia, it may become easier to determine the above mentioned diagnosis "impaired swallowing" in all patients having this problem.
Keywords: dysphagia; nursing diagnosis; impaired swallowing; screening for dysphagia